Analog and digital communication lecture notes 2017 - Weldon, Thomas Paul (E-Man Press, 2017)
This is the latest revision: May 20, 2020. The lecture notes in this book are a collection of presentation slides for teaching an undergraduate course in analog and digital communication systems. As lecture notes, this book is not intended to be a substitute for the many excellent textbooks in this field. Instead, this book is intended as a supplement to other course materials, and as a workbook for students taking notes during corresponding lectures. In addition, practicing engineers may find this book useful for quick review of the topic. Outline of the book: 1Introduction2Signals3Fourier Transform4Amplitude Modulation5Angle Modulation6Sampling and Probability7Digital Signals8Special Topics9Exam Reviews10Tables